Transport Granules Bound with Nuclear Cap Binding Protein and Exon Junction Complex Are Associated with Microtubules and Spatially Separated from eIF4E Granules and P Bodies in Human Neuronal Processes - Wang, Dan O.; Ninomiya, Kensuke; Mori, Chihiro; Koyama, Ayako; Haan, Martine; Kitabatake, Makoto; Hagiwara, Masatoshi; Chida, Kazuhiro; Takahashi, Shin-Ichiro; Ohno, Mutsuhito; Kataoka, Naoyuki (Frontiers in Molecular Biosciences, 2017)
RNA transport and regulated local translation play critically important roles in spatially restricting gene expression in neurons. Heterogeneous population of RNA granules serve as motile units to translocate, store, translate, and degrade mRNAs in the dendrites contain cis-elements and trans-acting factors such as RNA-binding proteins and microRNAs to convey stimulus-, transcript-specific local translation. Here we report a class of mRNA granules in human neuronal processes that are enriched in the nuclear cap-binding protein complex (CBC) and exon junction complex (EJC) core components, Y14 and eIF4AIII. These granules are physically associated with stabilized microtubules and are spatially segregated from eIF4E-enriched granules and P-bodies. The existence of mRNAs retaining both nuclear cap binding protein and EJC in the distal sites of neuronal processes suggests that some localized mRNAs have not yet undergone the “very first translation”, which contribute to the spatio-temporal regulation of gene expression.